Penerapan Algoritma Dijkstra dengan metode SAW dan Haversine Pada Pencarian Rute Terdekat Menemukan Titik Pemberhentian Angkot Kota Sukabumi - Zaldi Arif Mulkan; Iwan Rizal Setiawan; Fathia Frazna (Journal of Information System Research (JOSH), 2023)
Angkot (City Transportation) in Sukabumi City is a popular public transportation system and is one of the main means of transportation for local residents and visitors to move around in the city with so many lanes each that the angkot itself passes, 19 route routes which cause so many problems for the community and outsiders of Sukabumi in finding angkot stop points so that it slows down time and is inefficient. Therefore, to make it easier to find angkot stopping points, Dijkstra's algorithm was chosen. Dijkstra's algorithm is the shortest route search algorithm by relying on the smallest value weight and calculating all neighboring nodes to find the smallest value. Researchers used 2 methods used, namely the SAW and Haversine methods. SAW method (Simple Additive Weighting Method). This method is for carrying out weighted sums based on 3 criteria for road width, distance traveled and estimated time and then normalizing the data to ranking. the haversine method is to calculate distances based on lattitude and lontitude. Initiate from the starting point to the destination point with a graph using Dijkstra's algorithm to produce a 30 iteration focus point generated by Dijkstra's algorithm, then evaluate the model by reaching other paths to the destination point.The results obtained in the search for the closest route using the two SAW and Haversine methods, after calculating all the paths passed from the starting point V117 (Bayangkara Street) - V82 (R.E Martadinata Street) obtained the results of the shortest route obtained, namely V117 - V118 - V131 - V130 - V132 - V133 - V134 - V138 - V137 - V110 - V82. Looking for the closest route from the starting point to the destination location determined by the researcher with the final result in the form of a Web-based application.